Depression in youth recovering from concussion: Correlates and predictors. (16th April 2017) - Stazyk, Kathy; DeMatteo, Carol; Moll, Sandra; Missiuna, Cheryl
ABSTRACT: Objectives : Although depression can be a serious consequence of concussion, little is known about the factors that predict depression and concussion recovery outcomes in children. The purpose of this study was to explore the risk and possible predictors of developing significant depressive symptoms in children recovering from concussion. Methods : A prospective cohort study was conducted in a paediatric tertiary care clinic. Depression data were collected from 92 children using the Children's Depression Inventory-2 (CDI-2) screening tool. Correlations, t -tests and logistic regression were used to examine the associations between depression scores and demographic as well as injury-related factors. Results : Depressive symptoms were found in 22% of the children (T score on CDI-2 >65). Children with evidence of depressive symptomatology had significantly higher mean post-concussive symptom inventory (PCSI) scores in recovery ( p = 0.004) than children who were not depressed. Variables of i) Sex; ii) hospital admission; iii) number of head injuries; iv) post-concussion symptom score and v) experience of prolonged symptoms were predictive of clinically significant CDI T scores, explaining 36% of the variation in the binary logistic model. Conclusion : Depression is commonly reported in this subset of children. High post-concussive symptom scores and hospital admission were strong predictors of depression. Screening for depression should be standard practice in concussion management in children and youth.